(untitled) (Biological Sciences - PJSIR, 2006)
Variations in the systolic and diastolic blood pressures, and body weight were studied in 48 volunteers (24 males and 24 females), aged 25-55 years, beginning one week before, during the later days, and one week after the month of Ramadan. The observations were recorded in the morning and evening. The voluteers were divided in six age groups, which ranged between 25-30, 31-35, 36-40, 41-45, 46-50 and 51-55 years. The data of the three phases of the study showed no significant changes in the systolic and diastolic blood pressures and weight of the fasting individuals. There was a slight reduction in the mean weight during the third week of ‘Ramadan’, which in some cases was restored to normal levels immediately after the ‘Ramadan’ fasting. It has been concluded from the study that fasting has no adverse effect on the blood circulation and weight of healthy persons.